Enhancement of cryptography and transform domain in steganography for higher embedding capacity - Khalaf, Emad T (2012)
In the field of Data Communication, security issues are the top priority.Cryptography and steganography address the necessary elements for secure communication namely privacy, confidentiality,key exchange,authentication,and non-repudiation but reveals the fact that communication is happening.This study proposes a combination of Steganography and Cryptography to enhance security of the transmitted information.Hence this work is composed of two parts:cryptographic and steganographic.In the cryptographic part,an improvement has been proposed to the Hill cipher algorithm to be more secured by using a large and random key with large data block,and also extending it by including the special characters and digits.For the steganographic part,a new method has been proposed by combining Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT),to take the advantageous of both algorithms.The original image is decomposed into four bands using the Haar wavelet LL,HL,LH and HH.Three of these sub-bands have been selected to hiding data (LH,HL and HH)which are less effect to the image than LL sub-band.Then,DCT transform is applied to the selected DWT sub-band,the process of hiding will be in the least significant bit of the DCT coefficients to each sub-band. The distribution of data will be based on the chosen percentages,which is entered by a sender.These percentages will be agreed between both the sender and the receiver as a key of hiding.The proposed system goal is to provide more complexity in encryption and make the embedding capacity as high as possible with high visible quality in a way that it does not allow any attacker to even detect that there are secret messages.The complexity of encryption and concealment was checked out with a number of widely used metrics such as Peak Signal to Noise Ratio(PSNR),Mean Squared Error(MSE), Normalized Absolute Error (NAE) and Normalized Correlation Coefficient (NCC).The experimental results demonstrate the complexity of the proposed method compared with the standard and existing methods.